1988
DOI: 10.1093/ajcn/47.3.496
|View full text |Cite
|
Sign up to set email alerts
|

Iron supplementation and physical growth of rural Indonesian children

Abstract: The effect of oral iron supplementation on blood Fe levels and physical growth in 119 rural Indonesian school children was assessed in this double-blind study. The children were classified into anemic and normal groups according to their initial hemoglobin and transferrin saturation levels and were randomly assigned to either Fe or placebo treatment for 12 wk. Hematological, anthropometric, and morbidity data were collected before and after the treatment period. Before treatment, anemic subjects were smaller a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
75
1
7

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(87 citation statements)
references
References 22 publications
4
75
1
7
Order By: Relevance
“…Studies on the relationship between iron and growth (Aukett et al, 1986;Chwang et al, 1988;Angeles et al, 1993;Vihervuori et al, 1997;Persson et al, 1998;Scherriff et al, 1999) involved mainly iron de®cient and stunted children (Aukett et al, 1986;Chwang et al, 1988;Angeles et al, 1993;Vihervuori et al, 1997;Perrone et al, 1999) and con®rmed experimental studies (Dhur et al, 1989). A combined supplementation trial pointed to the potential synergy between iron and zinc effects on growth: it showed that iron is necessary to prime the growth-inducing effect of zinc in case of iron de®ciency (Perrone et al, 1999).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Studies on the relationship between iron and growth (Aukett et al, 1986;Chwang et al, 1988;Angeles et al, 1993;Vihervuori et al, 1997;Persson et al, 1998;Scherriff et al, 1999) involved mainly iron de®cient and stunted children (Aukett et al, 1986;Chwang et al, 1988;Angeles et al, 1993;Vihervuori et al, 1997;Perrone et al, 1999) and con®rmed experimental studies (Dhur et al, 1989). A combined supplementation trial pointed to the potential synergy between iron and zinc effects on growth: it showed that iron is necessary to prime the growth-inducing effect of zinc in case of iron de®ciency (Perrone et al, 1999).…”
Section: Discussionmentioning
confidence: 98%
“…It disappears in older infants when growth slows (Scherriff et al, 1999). The positive effect of iron on growth is emphasized by reports of iron supplementation of stunted and malnourished children (Aukett et al, 1986;Chwang et al, 1988;Angeles et al, 1993;Perrone et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the 3-month iron supplementation was not effective enough to correct iron de®ciency in all supplemented children. Moreover, each group contained iron-suf®cient children, who were expected not to respond, or to respond to a lesser degree to the iron supplementation than iron-de®cient children (Chwang et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Iron deficiency has detrimental effects on physical and mental development of young children and is irreversible when iron therapy is started after the critical period for development has elapsed (Kretchmer et al, 1996). In older children and adolescents, iron deficiency, with or without anaemia, interferes with learning capacity and school achievement (Bruner et al, 1996;Seshadri & Gopaldas, 1989) as well as with growth (Chwang et al, 1988;Lawless et al, 1994) and appetite (Lawless et al, 1994). In pregnancy, anaemia can lead to reduced intrauterine growth and thus to low birth weight and peri-natal mortality (Scholl & Hediger, 1994).…”
Section: Introductionmentioning
confidence: 99%